1989
DOI: 10.1161/01.res.65.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Fate of gap junctions in isolated adult mammalian cardiomyocytes.

Abstract: The fate of gap junctions in dissociated adult myocytes, maintained for up to 22 hours in culture medium, was investigated by semiquantitative analysis of thin sections and by freeze-fracture electron microscopy. Gap junctions in the dissociated myocyte are intact bimembranous structures seen either as invaginated surface-located structures or as annular profiles in the cytoplasm. Surface-located junctions are sealed from the exterior by a sheet of nonjunctional membrane originating (together with the "outer" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…Early ultrastructural analyses revealed large vesicular double-membrane GJ structures, AGJs, in the cytoplasm of cells derived from many different tissues (Ginzberg and Gilula, 1979;Larsen et al, 1979;Pfeifer, 1980;Leach and Oliphant, 1984;Mazet et al, 1985;Severs et al, 1989). Here, we demonstrate by expressing Cx43-GFP (a major GJ subunit protein) in HeLa cells, that entire GJ plaques can be internalized into one of the coupled cells to form these cytoplasmic, double-membrane GJ vesicles (Figure 1).…”
Section: Formation Of Double-membrane Gj Vesiclesmentioning
confidence: 60%
“…Early ultrastructural analyses revealed large vesicular double-membrane GJ structures, AGJs, in the cytoplasm of cells derived from many different tissues (Ginzberg and Gilula, 1979;Larsen et al, 1979;Pfeifer, 1980;Leach and Oliphant, 1984;Mazet et al, 1985;Severs et al, 1989). Here, we demonstrate by expressing Cx43-GFP (a major GJ subunit protein) in HeLa cells, that entire GJ plaques can be internalized into one of the coupled cells to form these cytoplasmic, double-membrane GJ vesicles (Figure 1).…”
Section: Formation Of Double-membrane Gj Vesiclesmentioning
confidence: 60%
“…Previous workers have characterized that this treatment, which results in the break-up of electrical and mechanical intercellular couplings, induces the formation of cytoplasmic gap junctional vesicles known as annular junctions. 21 That this increase in ZO-1 immunolocalization at internalized GJs is accompanied by increases in direct interaction between Cx43 and ZO-1 at the protein-protein level is supported by coimmunoprecipitation analyses. Taken together, our findings are consistent with the growing evidence 29,30 that previously hypothesized functions for MAGUK proteins (eg, ZO-1, dlg, PSD-95 and PSD-93) in active localization of proteins to membrane subdomains and in ion channel aggregation may need reevaluation, or at least, expansion to consider other possible modalities.…”
Section: Barker Et Al Cx43 and Zo-1 In Heart 321mentioning
confidence: 83%
“…Our data indicate that association between ZO-1 and Cx43 is surprisingly limited to low to moderate levels in intact ventricular myocardium. Furthermore, we find that disruption of intercellular contacts between myocytes, a treatment inducing gap junction endocytosis, 21 results in a dynamic change in the pattern of association between ZO-1 and Cx43. Our data suggests previously unanticipated roles for ZO-1 in the turnover of Cx43 during, or after, gap junctional endocytosis.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Annular gap junctions have been recognized as endocytosed fragments of gap junction plaques and early degradation products of gap junction membrane. 11,14,[26][27][28] Intracellular sites and pathways responsible for subsequent gap junction degradation have not been fully understood in cardiac cells, but previous molecular studies have suggested that both the lysosome and proteasome participate in cardiac gap junction degradation. 27,28 Gap junctions have a remarkably dynamic structure, because the turnover of connexin proteins is surprisingly rapid (the half-life of Cx43 in cardiac myocytes rages 1-2 h).…”
Section: Discussionmentioning
confidence: 99%